741. Antifungal Resistant Candida glabrata Are Most Commonly Colonized in Clostridioides difficile Infection (CDI) Patient Guts in Texas. (31st December 2020) - Begum, Khurshida; Haghighi, Farnoosh; Alam, M Jahanbgir; Garey, Kevin W; Garey, Kevin W
Abstract: Background: Candida glabrata is the second most common cause of invasive candidiasis in the United States. The echinocandin class of antifungals, including caspofungin has become the preferred therapy for invasive candidiasis due to C. glabrata and other species demonstrating decreased azole susceptibility. Caspofungin resistance has been uncommon, but reports suggest that the incidence is increasing, particularly among C. glabrata isolates. The dysbiosis associated with Clostridium difficile allows for overgrowth of Candida spp. However, the prevalence of C. glabrata in stool of C. difficile infection (CDI) patients is not well studied. Therefore, our objectives were to investigate the incidence of potentially pathogenic species of C. glabrata in stool samples of CDI patients. Methods: We collected 1, 241 Clostridioides difficile infection (CDI) patient stool samples from two large hospitals in Houston, Texas and enrich the samples in brain heart infusion (BHI) broth at 37C for 48-72 hours and then sub-cultured onto selective HardyChrom Candida agar and incubated at 37C for 48 to 72 hours. Characteristic Candida colonies were stocked in cryovials and kept at -80C for further analyses. Isolates were then identified by multiplex PCR. C. glabrata isolates were screened for caspofungin resistance on Muller-Hinton agar (with 8.0 ug/ml). Results: Overall, 14.8% (184/1241) samples were culture positive for Candida spp. The predominant species was C. glabrata (9.2 %) followed by C. albicans (2.3%), C. tropicalis (1.6%), C. parapsilosis (1.2%), C. krusei (0.6%) or not speciated (6.9%). The majority of C. glabrata isolates (70.2%; 80/114) were caspofungin resistant. Conclusion: The results of this study showed that colonization of C. glabrata is common in patients with CDI and could be a source of antifungal-resistant pathogens. Disclosures: All Authors : No reported disclosures